2019
DOI: 10.1136/bmjopen-2019-030559
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal effect of nocturnal R-R intervals changes on cardiovascular outcome in a community-based cohort

Abstract: RationaleSleep-disordered breathing (SDB) is strongly linked to adverse cardiovascular outcomes (cardiovascular diseases (CVD)). Whether heart rate changes measured by nocturnal R-R interval (RRI) dips (RRI dip index (RRDI)) adversely affect the CVD outcomes is unknown.ObjectivesTo test whether nocturnal RRDI predicts CVD incidence and mortality in the Wisconsin Sleep Cohort study (WSCS), independent of the known effects of SDB on beat-to-beat variability.MethodsThe study analysed electrocardiograph obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
1
15
0
2
Order By: Relevance
“…They found that the upper quartile of pulse rate changes was associated with increased cardiovascular morbidity and mortality risk. The main findings of the study corroborate our previous work on the WSCS (Wisconsin Sleep Cohort Study) using actual electrocardiogram-derived signal (R-R interval tracing) ( 2 ). However, the WSCS secondary analysis excluded individuals on chronotropic medications (e.g., a β-blocker or calcium channel blocker), which dampen the autonomic response to respiratory events and affect the sensitivity of the heart rate metric ( 3 ).…”
supporting
confidence: 87%
“…They found that the upper quartile of pulse rate changes was associated with increased cardiovascular morbidity and mortality risk. The main findings of the study corroborate our previous work on the WSCS (Wisconsin Sleep Cohort Study) using actual electrocardiogram-derived signal (R-R interval tracing) ( 2 ). However, the WSCS secondary analysis excluded individuals on chronotropic medications (e.g., a β-blocker or calcium channel blocker), which dampen the autonomic response to respiratory events and affect the sensitivity of the heart rate metric ( 3 ).…”
supporting
confidence: 87%
“…The mechanism may be that the autonomic nerve regulates the heart, and the vagal nerve tension increases; when the human body is in sleep, the vagal tone is increased, which leads to decreased concealed conduction and refractory periods in the atrioventricular junction. This then drives the propagation of the f-wave to the ventricle, thereby reducing the atrioventricular nodal hidden conduction, further increasing the rate of atrioventricular impulse transmission down to the ventricle and leading to higher fastest and slowest ventricular rates compared with the nonsleeping states [ 10 ]. Additionally, we observed a paroxysmal increase in the long R-R interval when the patients were not in sleep, while some patients were found to have long R-R intervals both in sleep and nonsleep periods (Supplementary Figures 3 and 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bradicich et al (238) and Wang et al (24) demonstrated associations between HRV and characteristics of polysomnographic parameters, however, they did not attempt to use HRV as a CVD risk predictor in this part of the SHHS dataset. Sankari et al (239) suggested beat-to-beat intervals index (RRDI) during sleep is closely correlated to new-diagnosis CVD (hazard ratio of 1.21 per 10-unit increment in RRDI) in OSA patients from the Wisconsin Sleep Cohort, but they did not utilize other linear and non-linear HRV measures to show the further relationship between CV risk and OSA.…”
Section: Hrv and Cardiovascular Mortality And Morbiditymentioning
confidence: 99%